Half pint/Puf68 is required for negative regulation of splicing by the SR splicing factor Transformer2. - Wang, S.; Wagner, E.J.; Mattox, W. (RNA Biology., 2013)
The SR family of proteins plays important regulatory roles in the control of alternative splicing in a wide range of organisms. These factors affect splicing through both positive and negative controls of splice site recognition by pre-spliceosomal factors. Recent studies indicate that the Drosophila SR factor Transformer 2 (Tra2) activates and represses splicing through distinct and separable effector regions of the protein. While the interactions of its Arg-Ser-rich activator region have been well studied, cofactors involved in splicing repression have yet to be found. Here we use a luciferase-based splicing reporter assay to screen for novel proteins necessary for Tra2-dependent repression of splicing. This approach identified Half pint, also known as Puf68, as a co-repressor required for Tra2-mediated autoregulation of the M1 intron. In vivo, Half pint is required for Tra2-dependent repression of M1 splicing but is not necessary for Tra2-dependent activation of doublesex splicing. Further experiments indicate that the effect of Hfp is sequence-specific and that it associates with these target transcripts in cells. Importantly, known M1 splicing regulatory elements are sufficient to sensitize a heterologous intron to Hfp regulation. Two alternative proteins deriving from Hfp transcripts, Hfp68, and Hfp58, were found to be expressed in vivo but differed dramatically in their effect on M1 splicing. Comparison of the cellular localization of these forms in S2 cells revealed that Hfp68 is predominantly localized to the nucleus while Hfp58 is distributed across both the nucleus and cytoplasm. This accords with their observed effects on splicing and suggests that differential compartmentalization may contribute to the specificity of these isoforms. Together, these studies reveal a function for Half pint in splicing repression and demonstrate it to be specifically required for Tra2-dependent intron inclusion.